2019
DOI: 10.1001/jamasurg.2018.3752
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Oncological and Functional Outcomes of Chemoradiotherapy Followed by Organ-Sparing Transanal Endoscopic Microsurgery for Distal Rectal Cancer

Abstract: for the CARTS Study Group IMPORTANCE Treatment of rectal cancer is shifting toward organ preservation aiming to reduce surgery-related morbidity. Short-term outcomes of organ-preserving strategies are promising, but long-term outcomes are scarce in the literature.OBJECTIVE To explore long-term oncological outcomes and health-related quality of life (HRQL) in patients with cT1-3N0M0 rectal cancer who underwent neoadjuvant chemoradiotherapy (CRT) followed by transanal endoscopic microsurgery (TEM). DESIGN, SETTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
157
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(181 citation statements)
references
References 50 publications
(74 reference statements)
10
157
3
1
Order By: Relevance
“…Ideal candidates are those with distally (<8-10 cm from the anal verge) located invasive tumors, favorable histology, and size <4 cm. [54][55][56] In such cases, it is critical that LE is performed by surgeons experienced with transanal LE techniques, preferably at centers with experienced multidisciplinary teams. It is important to note, however, TME conversion after LE for ypT2-3 may lead to major complications and poor functional outcomes.…”
Section: What Are the Indications For Neoadjuvant Rt For Operable Recmentioning
confidence: 99%
“…Ideal candidates are those with distally (<8-10 cm from the anal verge) located invasive tumors, favorable histology, and size <4 cm. [54][55][56] In such cases, it is critical that LE is performed by surgeons experienced with transanal LE techniques, preferably at centers with experienced multidisciplinary teams. It is important to note, however, TME conversion after LE for ypT2-3 may lead to major complications and poor functional outcomes.…”
Section: What Are the Indications For Neoadjuvant Rt For Operable Recmentioning
confidence: 99%
“…Stijns (14) reported on the functional results of patients with successful organ preservation in the CARTS study. They found that 50% of the patients had major LARS.…”
Section: Local Resection Of Rectal Cancer After Neoadjuvant Therapymentioning
confidence: 99%
“…In early stage tumours (C)RT can lead to OP in more than 50% when combined with local excision [13][14][15][16]. Unfortunately, this (C)RT can be accompanied by toxicity, morbidity and even mortality [14,15,17]. However, all available data on toxicity and mortality, are based on conventional radiotherapy techniques, with large treatment volumes, including large elective LN regions.…”
Section: Introductionmentioning
confidence: 99%